Electro-Optical Modulator Performance in SOl - Mardiana, Bidin; Hanim, Abdul Razak; Haroon, Hazura; Sahbudin, Saari; Menon, P.S; Abdullah, H. (2010)

(untitled)
Since 1980's, silicon photonic devices have been extensively studied, however a submicrometre-size photonic devices have been realized only in the last few years. Silicon properties namely the transparency in the range of optical telecommunications wavelengths and high index of refraction, have enabled the fabrication of low loss submicron waveguide. Photonic devices such as splitter, coupler, and filter have been demonstrated in silicon but once the device has been fabricated, the properties of the device are predetermined. A silicon based modulator can be used to control the flow of light, where the refractive index of the silicon waveguide can be varied thus, induce a change in the transmission properties. This paper highlights the study of carrier injection effect on silicon waveguide with p-i-n diode structure integrated on Silicon-on-Insulator (SOl). The device performance is predicted using 2D Silvaco CAD software under different applied voltages at 1.55 m.